Mandibular Ossifying Fibroma and Multiple Oral Papillomas in a Roe Deer (Capreolus capreolus) - Zürcher-Giovannini, Samoa; Ruder, Thomas-Daniel; Pool, Roy; Erdelyi, Karoly; Origgi, Francesco C. (Frontiers in Veterinary Science, 2020)
An emaciated, adult, free-ranging roe deer (Capreolus capreolus) presenting a large mandibular mass, was shot by a game warden in Sissach, Switzerland. The head of the roe deer was submitted to the Centre for Fish and Wildlife Health for examination. Grossly, the mass consisted of a 6 × 7 × 4 cm mandibular exophytic growth, associated with loss of incisors teeth. On cut section, a hard, light-tan core was rimmed by a thick layer of soft tissue. Computed tomography examination confirmed the mandibular origin of the mass. Histologically, the mass consisted of an unencapsulated fibro-osseous neoplasm. The bony portion was composed of multiple haphazardly arranged spicules rimmed by osteoblasts with no associated periosteal layer. Embedding the bony spicules were short anastomosing and branching streams and bundles of spindled cells. The overlaying partially ulcerated mucosa, showed prominent rete ridges deepening into the submucosa. In addition to the mandibular mass, multiple soft cauliflower-like proliferations were expanding from the gingival surface. Histologically, these masses were arranged in papillary elements composed of pluristratified squamous epithelium with long rete ridges extending into a rich underlying fibrovascular supportive stroma. Neither papillomaviral DNA nor antigen could be identified in association with the oral masses. The gross, histological and radiological features of the mandibular mass are consistent with an ossifying fibroma, while the cauliflower oral masses were diagnosed as papillomas.